STUDIES ON CERTAIN BLOOD BIOCHEMICAL CONSTITUENTS IN NORMAL AND REPEAT BREEDING CROSSBRED COWS - ZAMAN, MALIK IMRANUL; SHARMA, UTSAV; RAZZAQUE, W A A; KUMAR, SUDHIR; KUMAR, SHARAD (The Indian Journal of Animal Reproduction, 2023)
The biochemical profile of 45 repeat breeding crossbred cows cycling regularly and showing positive reaction to white side test and 1 O normal crossbred cows were analyzed and result revealed that the difference in mean value of total plasma protein, albumin and globulin were non-significant in both the groups. However, albumin / globulin ratio was non-significantly higher in repeat breeder (0.80 ± 0.07) than the normal (0.68 ± 0.14) cows. Total plasma cholesterol was non-significantly higher in normal (125.6 ± 4.86 mg/di) than repeat breeder (117.35 ± 2.31 mg/di) cows.